Effect of point mutations on the ultrafast photo-isomerization of Anabaena sensory rhodopsin - Agathangelou, Damianos; Roy, Partha Pratim; Buckup, Tiago (Photoinduced processes in nucleic acids and proteins, 2018)
Anabaena sensory rhodopsin (ASR) is a particular microbial retinal protein for which light-adaptation leads to the ability to bind both the all-trans, 15-anti (AT) and the 13-cis, 15-syn (13C) isomers of the protonated Schiff base of retinal (PSBR). In the context of obtaining insight into the mechanisms by which retinal proteins catalyse the PSBR photo-isomerization reaction, ASR is a model system allowing to study, within the same protein, the protein-PSBR interactions for two different PSBR conformers at the same time. A detailed analysis of the vibrational spectra of AT and 13C, and their photo-products in wild-type ASR obtained through femtosecond (pump-) four-wave-mixing is reported for the first time, and compared to bacterio- and channelrhodopsin. As part of an extensive study of ASR mutants with blue-shifted absorption spectra, we present here a detailed computational analysis of the origin of the mutation-induced blue-shift of the absorption spectra, and identify electrostatic interactions as dominating steric effects that would entail a red-shift. The excited state lifetimes and isomerization reaction times (IRT) for the three mutants V112N, W76F, and L83Q are studied experimentally by femtosecond broadband transient absorption spectroscopy. Interestingly, in all three mutants, isomerization is accelerated for AT with respect to wild-type ASR, and this the more, the shorter the wavelength of maximum absorption. On the contrary, the 13C photo-reaction is slightly slowed down, leading to an inversion of the ESLs of AT and 13C, with respect to wt-ASR, in the blue-most absorbing mutant L83Q. Possible mechanisms for these mutation effects, and their steric and electrostatic origins are discussed.
Published on 15 November 2017
Gesehen am 08.05.2019